Modeling of pneumonozzle system work - Rivna, Katerina; Gavva, Oleksandr M.; Kryvoplias-Volodina, Liudmyla (My University, 2019)
The purpose of the study is to develop a formalized approach to the simulation of kinematic and dynamic analysis of a pneumatic blower unit of the ejection type in the environment of PP FluidSim with CFD modeling.
Keywords: пакування; пневматика; сопло; тиск; пневматика; сопло; packing; pneumatics; nozzle; pressure; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв